PENEGAKAN SANKSI ADMINISTRASI TERHADAP APARATUR SIPIL NEGARA YANG MELAKUKAN KEJAHATAN JABATAN OLEH PEJABAT PEMBINA KEPEGAWAIAN PEMERINTAH PROVINSI BENGKULU - Miinudin Miinudin; Etry Mike (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: The Bengkulu Provincial Government is strongly committed to improving the quality of the Apparatus Resources of bureaucratic reform, especially the reform of apparatus resources within the Regional Government of Bengkulu Province. The ASN task has been regulated in Article 11 of the ASN Law stated that ASN employees are in charge of: a. Carry out public policies made by Personnel Development Officers in accordance with statutory provisions; b. provide professional and quality public services; and c. Strengthen the unity and unity of the Unitary State of the Republic of Indonesia. In order to carry out its duties, violations often occur that might interfere with public services which should be prioritized in carrying out their duties. Government Regulation Number 11 of 2017 concerning Civil Servants Management is regulated regarding dismissal of civil servants without respect if: "convicted with imprisonment or confinement based on a court decision that has permanent legal force because of a crime of occupation crime or crime related to General position and/or criminal.Keywords: Enforcement, Sanctions, Administration, State Civil Apparatus, Position Crimes